Antibiotic Sensitivity Test Against Soil Bacteria Exposed to Disinfectants in 2x11 Kayu Tanam District, Padang Pariaman Regency, West Sumatera - Prima, Rika; Vestimarta, Aldi Wahyuda; Putri, Dwi Hilda (Department of Biology, Faculty of Mathematics and Natural Sciences, Universitas Negeri Padang, 2024)
In Indonesia, the population growth rate is high and requires rapid and sustainable improvements in the agricultural sector. Improvements in the agricultural sector require various supporting facilities, namely agricultural tools, fertilizers, chemicals including pesticides. Pesticides are chemicals or mixtures of several chemicals that are used to control or eradicate plant pest organisms. Specific uses are an inseparable part of the agricultural system. Pesticides are used as a preventive measure to control pests/diseases. The research carried out included testing on soil samples, testing bacterial turbidity, and testing inhibition zones using antibiotics. This research is descriptive research. This research was carried out from March to June 2023, at the Research Laboratory, Department of Biology, Faculty of Mathematics and Natural Sciences, Padang State University. From the research carried out on soil sample tests, what was observed was the color, shape, height and edges of each different type of bacterial colony. The turbidity test was obtained in accordance with Macfarlan standards. Then the zone inhibition test uses antibiotics which use positive, negative and spectrum antibiotics. From the table of inhibition zones that are formed, it can be seen that in each bacterial colony, each antibiotic works according to the type of antibiotic, positive antibiotics inhibit the growth of gram-positive bacteria and negative antibiotics inhibit the growth of gram-negative bacterial colonies, while spectrum antibiotics can inhibit the growth of gram-positive bacteria and bacteria. gram negative.